RIBOSE PHOSPHATE ISOMERSASE 1 Influences Root Development by Acting on Cell Wall Biosynthesis, Actin Organization, and Auxin Transport in Arabidopsis - Huang, Jia-Bao; Zou, Yi; Zhang, Xiaojing; Wang, Mingyan; Dong, Qingkun; Tao, Li-Zhen (Frontiers in Plant Science, 2020)
Cell wall biosynthesis plays essential roles in cell division and expansion, thus fundamental to plant growth and development. In this work, we show that an Arabidopsis mutant dpr3, isolated by a forward genetic screen, displays embryo defects and short, swelling primary root with the failure of maintenance of root apical meristem reminiscent to several cell wall-deficient mutants. Map-based cloning identified dpr3 is a mutant allele of RIBOSE PHOSPHATE ISOMERSASE 1 (RPI1), an enzyme involved in cellulose synthesis. Cellulose content in the mutant was dramatically decreased. Moreover, dpr3 (rpi1 from hereon) caused aberrant auxin distribution, as well as defective accumulation of root master regulators PLETHORA (PLT1 and PLT2) and misexpression of auxin response factor 5 (MONOPTEROS, MP). The abnormal auxin distribution is likely due to the reduced accumulation of auxin efflux transporters PIN-FORMED (PIN1 and PIN3). Surprisingly, we found that the orientation of actin microfilaments was severely altered in rpi1 root cells whereas the cortical microtubules stay normal. Our study provides evidence that the defects in cellulose synthesis in rpi1 affects polar auxin transport possibly connected with altered F-actin organization, which is critically important for vesicle trafficking, thus exerting effects on auxin distribution, signaling, and auxin-mediated plant development.